Voluntary risk reporting to enhance institutional and organizational legitimacy: evidence from Portuguese banks - Oliveira, J. (2017)
This paper aims to explore the factors that affected the voluntary risk‐related disclosures (RRD) in the individual annual reports for 2006 of Portuguese banks. It also explores the extent to which those reports conformed to Basel II requirements in terms of the voluntary disclosure of operational risk and capital structure and adequacy matters. The authors conduct a content analysis of the annual reports of a sample of 111 banks. Voluntary operational risk and capital structure and adequacy disclosures were assessed using a list of disclosure categories that were developed from the Third Pillar disclosure requirements of the Basel II Accord. Stakeholder monitoring and corporation reputation are crucial factors that explain the risk reporting practices observed. Voluntary risk reporting appears to enhance legitimacy for two major reasons: first, by fulfilling institutional pressures to assure the effectiveness of market discipline; and second, by managing stakeholder perception of a corporation's reputation. The voluntary RRD observed are shown to be explained by legitimacy theory and resources‐based perspectives. This theoretical framework has not been tested hitherto in explaining the motives for banks to make voluntary RRD.